2005
DOI: 10.1002/cncr.21569
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fluor‐18‐deoxyglucose‐positron emission tomography in the management of colorectal liver metastases

Abstract: Fluor-18-deoxyglucose-positron emission tomography (FDG-PET) has emerged as a promising diagnostic modality in recurrent colorectal carcinoma. Wholebody FDG-PET may be an accurate diagnostic modality to determine whether patients with recurrent hepatic disease are suitable candidates for curative resection. Reports on the use of FDG-PET in patients with recurrent colorectal carcinoma are scarce, especially those on colorectal liver metastases. To assess the usefulness of this emerging modality for the selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
126
2
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(139 citation statements)
references
References 49 publications
5
126
2
6
Order By: Relevance
“…CT has previously been established as a way to evaluate response to chemotherapy treatment in solid tumors as defined by the Response Evaluation Criteria in Solid Tumors (RECIST) criteria [25]. FDG-PET, due to its superior sensitivity in detecting extrahepatic disease, is extremely useful in reducing the number of futile operative procedures performed in patients with otherwise occult metastatic disease [26][27][28][29]. The utility of this preoperative study was also shown by Strasberg et al [30] to lessen tumor recurrence in a chemo-naïve patient cohort undergoing hepatic resection for colorectal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…CT has previously been established as a way to evaluate response to chemotherapy treatment in solid tumors as defined by the Response Evaluation Criteria in Solid Tumors (RECIST) criteria [25]. FDG-PET, due to its superior sensitivity in detecting extrahepatic disease, is extremely useful in reducing the number of futile operative procedures performed in patients with otherwise occult metastatic disease [26][27][28][29]. The utility of this preoperative study was also shown by Strasberg et al [30] to lessen tumor recurrence in a chemo-naïve patient cohort undergoing hepatic resection for colorectal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…18 Fluorodeoxyglucose positron emission tomography (FDG-PET) detects changes in glucose uptake and metabolism, and also provides information about the location of a cancer within tissues. It is now considered to be a sensitive and accurate technique, and several studies have suggested that it should be carried out before resection of liver metastases from CRC van der Hiel et al, 2001;Fernandez et al, 2004;Truant et al, 2005;Wiering et al, 2005;Khan et al, 2006).…”
mentioning
confidence: 99%
“…23 In a recent meta-analysis, 24 both the sensitivity and the specificity of FDG-PET imaging for the detection of extrahepatic lesions exceeded 90%, as compared with only 60.9% and 91.1%, respectively, for CT. Furthermore, a systematic review 25 of FDG-PET imaging results in patients with colorectal liver metastasis has revealed that FDG-PET may detect extrahepatic disease not identified by other modal- In the past, almost all initially unresectable patients were treated by systemic or locoregional chemotherapy, which yielded 5-year survival rates less than 5%.…”
Section: Discussionmentioning
confidence: 99%